A contribution to studying the effect of some parameters on the analytical behavior of reinforced concrete coupling beams subjected to wind loads - بشور سارة; حويجة بسام; عيسى فدوى (Latakia University Journal -Engineering Sciences Series, 2023)
In recent years, Performance-Based Wind Design has begun to allow nonlinear response for specific structural elements, and studies are still in progress to investigate the behavior of these elements such as coupling beams when subjected to wind loads. Coupling beams in coupled shear wall systems have the ability -through their nonlinear behavior- to dissipate energy and reduce the forces transmitted to shear walls and foundations. This analytical study aims to investigate the effect of some important parameters on the behavior of conventional reinforced concrete coupling beams when exposed to wind loads, where the effect of aspect ratio and yield strength of longitudinal reinforcing steel was studied. Results showed that the aspect ratio had an effect on the strength and stiffness of the beams, as for residual displacements and the pinching effect, no significant change was observed with the change of the aspect ratio. As for the yield strength of reinforcing steel, the most significant change was noticed in the maximum strength, where the difference in the strength of the beams has reached an approximate value of 15%.